Novel, bioactive film based on methylcellulose incorporated with quercetin-loaded nanoparticles: Bifunctional antioxidant and ultraviolet-shielding properties - Nantapreecha, Kanthika; Pratheepthinthong, Supoj; Sane, Amporn; Suppakul, Panuwat (Agriculture and Natural Resources, 2022)
A novel, bifunctional nanocomposite methylcellulose (MC) film was developed with antioxidant and ultraviolet (UV)-shielding properties. Quercetin (QC) nanoparticles (NPs) with an average size of approximately 60 nm were generated using a rapid expansion process. Quantification of the total phenolic content (TPC) was performed, followed by three assays—2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, 2,2’-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) radical cation decolorization and ferric reducing antioxidant power (FRAP)—to investigate the antioxidant effectiveness of the QC-NPs. The QC-NPs had a TPC value of 1,619.59 μg gallic acid equivalents/mg and high antioxidant activities. The QC-impregnated MC films with all treatments (impregnated with ethanol (QC-EtOH)-, nanoparticles (QC-NPs) or water (QC-H2O-MC) with concentrations of 0.1–0.5% w/w) were fabricated using the solution casting technique and characterized. The addition of QC into the MC films was substantiated using Fourier transform infrared spectroscopy. Impregnation of the QC-NPs into the MC film demonstrated that the QC-NPs augmented the antioxidant activities of QC and substantially improved the UV-shielding property of the MC film.